ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI USAHATANI SINGKONG DI KECAMATAN BANJAR MARGO, KABUPATEN TULANG BAWANG PROVINSI LAMPUNG - Adriani, Dessy; Widiastuti, Ari; Purbianti, Erni (JURNAL AGRIMANSION, 2025)
The use of production factors with the right dosage in cassava farming can affect cassava production. The efficiency of the use of each production factor needs to be achieved to optimize production and income in cassava farming. This study aims to analyze the factors that affect cassava farming and examine the efficiency of the use of production inputs used. The selection of the research location used the purposive sampling method while the sample withdrawal used the Disproportional Stratified Random Sampling method. The population in this study is cassava farmers in Purwa Jaya Village as many as 233 farmers and Mekar Jaya Village as many as 292 farmers. Based on the characteristics of the respondents who were adjusted, 50 respondents were obtained from cassava farmers. Primary data in this study were collected by means of a survey using questionnaires and analyzed using regression with the function of Cobb-Douglas type production equations. The results of the study show that the factors that significantly affect cassava production are land area, seeds, urea fertilizer and farming experience. The production factors in technically efficient cassava farming are land area, seeds, urea fertilizers, NPK fertilizers, organic fertilizers, insecticides, and labor. Production factors in cassava farming that can be increased to achieve optimal production allocatively are land area, seeds, urea fertilizer, and insecticides.